2004
DOI: 10.1021/bc049920n
|View full text |Cite
|
Sign up to set email alerts
|

DNA Complexing Lipopolythiourea

Abstract: We present a neutral lipopolythiourea (DTTU) as a potential DNA-binding agent. Light scattering experiments showed that mixing a lipopolythiourea with dipalmitoylphosphatidylcholine (DPPC/DTTU) led to small particles with sizes ranging from 100 to 150 nm at optimum conditions. Setting a fixed DNA amount, an increasing amount of DTTU/DPPC or DPPC lipids was added. Particle size increased only with DTTU/DPPC, indicating that interaction occurred between the DTTU/DPPC particles and DNA. In the same way, only DTTU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Despite this major drawback, DT3TU could be formulated with dipalmytoylphosphatidylcholine (DPPC) or PEG-lipid to avoid aggregation, and obtain a formal proof of concept of the maintained thiourea function capacity to interact with DNA in its lipidic form [19]. When associated to DT3TU, DNA was protected from DNAse-mediated degradation [19], and transfection of HeLa cells was achieved (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this major drawback, DT3TU could be formulated with dipalmytoylphosphatidylcholine (DPPC) or PEG-lipid to avoid aggregation, and obtain a formal proof of concept of the maintained thiourea function capacity to interact with DNA in its lipidic form [19]. When associated to DT3TU, DNA was protected from DNAse-mediated degradation [19], and transfection of HeLa cells was achieved (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the above mentioned advantageous properties of the thiourea moiety, we therefore chose to incorporate this function at the polar head of a lipid, in order to form lipothiourea-based liposomes [19]. We could show that the thiourea function maintained its property of interacting with phosphates in a lipidic form.…”
Section: Introductionmentioning
confidence: 99%
“…However, this does not reflect all the mechanisms of interaction between thiourea lipids and DNA as compound 1b which only bears thiourea functions is able to interact with DNA although less efficiently. The compounds from the "lysine" lipopolythiourea family [16][17][18] which are also able to compact DNA do not undergo acidic conditions during their synthesis which implies that DNA compaction does not necessarily need electrostatic interactions. The lysine structure of this family of compounds might induce rigidity in the lipid structure which surely affects the DNA compaction.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that different families of lipopolythioureas could compact DNA [16] and transfect cells [17]. We improved the structure of the lipids until the molecules were hydrophilic enough to be easily formulated.…”
Section: Introductionmentioning
confidence: 99%
“…We recently developed non cationic lipids based on a thiourea head group moiety (LPT) [16]. We investigated various lipid chain lengths, types of linker and structures of the head group in order to optimize the formulation and transfection properties [17].…”
Section: Introductionmentioning
confidence: 99%